Intimal hyperplasia induced by vascular intervention causes lipoprotein retention and accelerated atherosclerosis. Issue 14 (17th July 2017) - Kijani, Siavash; Vázquez, Ana Maria; Levin, Malin; Borén, Jan; Fogelstrand, Per
Abstract: Accelerated atherosclerosis diminishes the long term patency of vascular interventions, such as percutaneous coronary intervention and implantation of saphenous vein grafts. However, the cause of this accelerated atherosclerosis is unclear. In this study, we tested the hypothesis that intimal hyperplasia formed following vascular intervention promotes retention of atherogenic lipoproteins. Intimal hyperplasia was surgically induced in the mouse common carotid artery. The surgery was combined with different mouse models of hypercholesterolemia to obtain different cholesterol levels and to control the onsets of hypercholesterolemia. Three weeks after surgery, samples were immunostained for apoB lipoproteins, smooth muscle cells and leukocytes. Already at mild hypercholesterolemia (193 mg/dL), pronounced apoB lipoprotein retention was found in the extracellular matrix in both intimal hyperplasia and the injured underlying media. In contrast, minimal retention was detected in the uninjured proximal region of the same vessel, or in vessels from mice with normal cholesterol levels (81 mg/dL). Induction of aggravated hypercholesterolemia 3 weeks after surgery, when a mature intimal hyperplasia had been formed, caused a very rapid development of atherosclerotic lesions. Mechanistically, we show that lipoprotein retention was almost exclusively dependent on electrostatic interactions to proteoglycan glycosaminoglycans, and the lipoprotein retention to intimal hyperplasia could be inhibited in vivo using glycosaminoglycan‐binding antibodies. Thus, formation of intimal hyperplasia following vascular intervention makes the vessel wall highly susceptible for lipoprotein retention and accelerated atherosclerosis. The increased lipoprotein retention in intimal hyperplasia can be targeted by blocking the interaction between apoB lipoproteins and glycosaminoglycans in the extracellular matrix. Abstract : Vascular interventions are associated with rapid formation of atherosclerotic lesions. This study shows that intervention‐induced intimal hyperplasia makes the vessel wall highly susceptible for lipoprotein retention and accelerated atherosclerosis. Furthermore, the increased lipoprotein retention in intimal hyperplasia can be targeted by LDL‐mimicking peptides and immunization with glycosaminoglycan‐binding antibodies.